Nodulation efficiency by native rhizobia from nodules of Pisum sativum "pea" collected from different Departments of Peru - Moreno-Chirinos, Zoila E. (2016)
In the present investigation was able to authenticate the ability to nodulate and to evaluate the frequency of nodulation efficiency of 50 isolate strains of pea nodules, collected from the departments: La Libertad, Lambayeque, Cajamarca and Lima. Which was inoculated to 1 mL of culture suspension alone (1.2x109 cel /mL) in seedlings of Pisum sativum var. Selection Junín, keeping them under conditions of relative humidity,50-70% and temperature / photoperiod, 28 °C – 24 °C / 14 h – 10 h (light-dark). At 25 days post-inoculation was obtained that 40% nodulated the host plant. To determine the frequency of nodulation efficiency, we took into account the parameters of speed of nodulation (DN in mm) and the percentage of roots nodulated (PRN%); pearson correlational analysis of the 5% significance, MANOVA and Tukey statistical DHS, allowed to establish the ranges (high, medium and low) for DN and PRN% for each crop, resulting in only 10% of all crops (Ra Ra 218-01 and 212-01) showed high efficiency in nodulation, as DN were high and high PRN%.